Caught by surprise - Turano, Jen (Turano, Jen. Apart from the crowd., 2018)
"After years of hiding her true nature, Miss Temperance Flowerdew is finally enjoying freedom outside of the shadow of her relations, so the last thing she expected on her way to work was to be grabbed off the street by a stranger and put on a train bound for Chicago. When Mr. Gilbert Cavendish is called upon to rescue a missing woman, he follow the trail to Chicago only to discover that the woman is his good friend, Temperance. Before they can discover who was behind her abduction, they're spotted alone together by a New York society matron, putting their reputations at risk. Even though Gilbert is willing to propose marriage, Temperance is determined not to lose her newfound independence. But when the misunderstanding in Chicago escalates into a threat on her life, accepting Gilbert's help in solving the mystery may lead to more than she ever could have dreamed."--Page [4] of cover.